Dayah Ruhul Falah Samahani Education System Aceh Besar District - Yusran Yusran; Kasuwi Saiban2; Zainur Rozikin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
To achieve this goal, it is necessary to have an integrated education system implemented by several Acehnese Islamic boarding schools so that students have various life skills, are creative, independent, and become noble citizens. From this description, the traditional education system in Aceh has experienced very drastic changes, and these changes are still continuing because the shape and education system are still felt to have not met the expectations of the public. Dayah Ruhul Falah Samahani's education system has also undergone changes by integrating the curriculum in accordance with the general education system with the aim of giving birth to a generation that can master Imtaq and Science and Technology, so that Dayah Ruhul Falah Samahani becomes an alternative for the community to make a place to educate their children. The research method used in this study is a qualitative method. Through qualitative methods researchers want to gain an understanding and deep thought about social reality and facts that are relevant to changes in the Dayah education system. In line with the above purpose, Creswell (2010) suggests that qualitative research is "methods for exploring and understanding the meaning that some individuals or groups of people ascribe to social or humanitarian problems". Data collection is done through observation, interviews and document review. As for the internal obstacle in the change in Dayah education system, it is caused by the first factor of the family of Dayah leaders who are still less supportive and also some of the Dayah teachers who are still difficult to accept changes. Furthermore external constraints relate to the perception of other Dayah leaders who are negative and there is no longer any contribution either from the staff or the budget from the community.